Гуцульсько-західнополіські лексичні паралелі (на матеріалі прізвиськ жителів Західного Полісся) - Шульська, Наталія Миколаївна; Shulska, Nataliia M. (Прикарпатський національний університет імені В. Стефаника, 2012)
На матеріалі неофіційної антропонімії Західного Полісся (прізвиськ) проведено гуцульсько-західнополіські лексичні паралелі, простежено семантику лексем – твірних основ прізвиськ і відповідність їх мотиваційній характеристиці; окремо виділено семантично різні діалектизми Гуцульщини і Західного Полісся. Описано прізвиська, твірною базою яких слугувала гуцульська лексика, не зафіксована в західнополіських говірках. Такі прізвиська цікаві, оскільки дозволяють простежити ментальний уклад іншого регіону.

On the material unofficial antroponimia of Western Polessya (nicknames) held Huzul-Western lexical parallels traced semantics tokens – generators and bases nicknames match their motivational characteristics, separately allocated semantically different dialectisms Huzulshcyna and Western Polessya. We describe the nicknames, which served as a basis of generators Huzul language is not recorded in the Western Dialect. These nicknames are interesting, as they allow to trace the mental way of another region.
Guzul-western lexical parallels (on the nicknames of Western Polissya)
Keywords: прізвисько; гуцульська мова; Гуцульщина; Західне Полісся; лексичні паралелі; nickname; Huzul language; Huzulshcyna; Western Polessya; lexical parallels; 811.161.2’282.2’373/23(477.8)